Asymmetric maltose neopentyl glycol amphiphiles for a membrane protein study: effect of detergent asymmetricity on protein stability. Issue 4 (14th November 2018) - Bae, Hyoung Eun; Du, Yang; Hariharan, Parameswaran; Mortensen, Jonas S.; Kumar, Kaavya K.; Ha, Betty; Das, Manabendra; Lee, Hyun Sung; Loland, Claus J.; Guan, Lan; Kobilka, Brian K.; Chae, Pil Seok
Abstract : An asymmetric MNG, MNG-8, 12, provided enhanced stability to human G protein-coupled receptors (GPCRs) compared to the symmetric MNG, MNG-3. Abstract : Maintaining protein stability in an aqueous solution is a prerequisite for protein structural and functional studies, but conventional detergents have increasingly showed limited ability to maintain protein integrity. A representative novel agent, maltose neopentyl glycol-3 (MNG-3), has recently substantially contributed to membrane protein structural studies. Motivated by the popular use of this novel agent, we prepared asymmetric versions of MNG-3 and evaluated these agents with several membrane proteins including two G protein-coupled receptors in this study. We found that some new MNGs were significantly more effective than MNG-3 at preserving protein integrity in the long term, suggesting that these asymmetric MNGs will find a wide use in membrane protein studies. In addition, this is the first study addressing the favorable effect of detergent asymmetric nature on membrane protein stability.